Association of ABO, Lewis and Secretor Phenotypes and Genotypes with Neisseria gonorrhoeae - Perry, Elizabeth Holly (Auckland University of Technology, 2003)
Previous studies of association of ABO phenotypes with gonorrhoea have shown contradictory results. Despite the interdependencies, none have examined the combined effect of ABO, Lewis and Secretor phenotypes. Furthermore, none have used genotyping to confirm phenotyping. This study is ground-breaking in this regard, and illustrates how such an association study should be performed. STUDY DESIGNS AND METHODS: The study examined 175 individuals who tested positive for gonorrhoea, and 211 individuals who tested negative for gonorrhoea. Strain typing was not performed. The following blood grouping methods were performed on the study participants: ABO phenotyping Lewis phenotyping, and genotyping of selected samples Secretor genotyping Chi-square and p values were used to examine whether or not there is an association of ABO, Lewis and Secretor blood group related molecules with gonorrhoea infection. RESULTS: Neither random statistical analysis of data sets, nor statistical analysis of data sets arranged by blood group, yielded a statistically significant association of ABO, Lewis and Secretor phenotypes and genotypes with Neisseria gonorrhoeae that could not be refuted when the data was disaggregated for ethnicity. The study did show a statistically significant difference in the incidence of the partial secretor phenotype (26.7%) in the gonorrhoea positive population and the incidence of the partial secretor phenotype (15.4%) in the gonorrhoea negative population, when all ethnic groups were analysed together. However, when the data was disaggregated for ethnicity, the p values were no longer statistically significant. CONCLUSION: There is no association of ABO, Lewis and Secretor phenotypes and genotypes with Neisseria gonorrhoeae. Nevertheless, this study still has merit, because, to the author's knowledge, it is the first time a study of these human blood groups with a disease has been performed correctly.
Keywords: Phenotype; Gonorrhea; Health studies